Study of Sea Water Quality Status in the Saugi Island Area, Pangkep Regency: Analysis of the Impact on Marine Biota - Nasrul, Nasrul; Nur, Medar M; Wahyuni, Rara Sri; Nuryadi, Nuryadi; Pratama, Muhammad Faiz; Ananda, Wangi Suci; Ningsih, Isna Sulistia; Maru, Rosmini (Program Pascasarjana Universitas Sriwijaya, 2024)
This research aims to analyze the quality of marine waters in the Saugi Island area, North Liukang Tupabbiring District, Pangkep Regency, and its impact on marine biota. This research uses a descriptive quantitative approach by processing data from field measurements and laboratory tests on several parameters. Furthermore, the test results will be compared with the standard requirements for seawater quality for the needs of marine biota by referring to the Decree of the Minister of the Environment No. 51 of 2004. In addition, a spatial analysis is carried out to see the predicted concentration distribution pattern for each measurement parameter. each of these parameters. The research results show that of the 10 research stations, only station 4 meets several seawater quality standards. The presence of waste at each station plays a significant role in reducing the value of quality parameters. In conclusion, the quality of seawater on the coast of Saugi Island is not good for marine biota. Therefore, efforts are needed to maintain the cleanliness of the coastal environment so that air quality is maintained, supports the life of marine biota, increases catches, and the potential for sustainability of marine ecosystems.